Evaluasi Kebijakan Dana Bantuan Operasional Sekolah (BOS) Pada Sekolah Dasar: Studi Kasus SD Inpres Kiwangona Kecamatan Adonara Timur Kabupaten Flores Timur - Maria Agustina Deran Narek; Petrus Kase; Alfred O. Ena Mau (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
This study aims to evaluate the effectiveness of the School Operational Assistance (BOS) Fund management at SD Inpres Kiwangona as an implementation of public policy in basic education. The BOS Fund serves as a government policy instrument to promote equitable access and improve the quality of education, particularly in remote areas. This research applies a qualitative descriptive approach using the input, process, output and outcome (IPOO) evaluation model. Data were collected through observation, documentation, and analysis of financial and administrative reports related to BOS fund utilization. The results show that in the input aspect, SD Inpres Kiwangona has adequately prepared human resources and administrative tools for BOS management. The process aspect demonstrates that fund management follows official technical guidelines through planning, disbursement, utilization, and accountable reporting stages. The output aspect indicates significant improvements in educational services, such as the availability of learning facilities, extracurricular activities, and increased student motivation. Meanwhile, the outcome aspect shows that the BOS program contributes to higher student achievement, a more conducive learning environment, and reduced financial burdens on parents. Overall, the BOS policy implementation at SD Inpres Kiwangona has been relatively effective, although some challenges remain, including reporting constraints and delayed fund disbursements. These findings highlight the need for enhanced school management capacity and continuous government support to ensure the sustainability and accountability of the BOS program in improving educational quality in remote regions.